THE RHETORICAL STRUCTURE AND LINGUISTIC FEATURES IN ISLAMIC STORIES OF PROPHETS - Diana Sopha; Vera Kristiana (IKIP Siliwangi, 2022)
The study discusses how this Prophet stories writing is structured and its linguistic features by using descriptive method. The writing of Prophet stories is started by an introduction, followed by body of essay and the final paragraph is the conclusion as the closing of the story. The introduction provides some general idea related to the topic discussed then the body of essay discusses the specific ideas of the topic or the sequence of events occurred in the story. The last paragraph of the story is the conclusion provides suggestions, offer and commands to the people as the readers because there are some valuable moral lessons to take based on the ideas/meaning of the stories of the Prophet. Based on the linguistic features, the stories of the Prophet mainly use some tenses. Simple Past is used to describe the past events/activities occurred in the era of the Prophet and Present tense is used to describe fact or general truth and nowadays situation. Besides, the meaning or ideas of the stories are written mostly in statement (declarative sentence) in active voice but a few sentences are written in passive voice. Some ideas are also written in interrogative sentence (questions) found in introduction and imperative sentence (command) in the conclusion paragraph. Keywords: Rhetorical Structures, Linguistic Features, Islamic Prophet Stories